Fines migration in geothermal reservoirs: Laboratory and mathematical modelling. (January 2019) - You, Z.; Badalyan, A.; Yang, Y.; Bedrikovetsky, P.; Hand, M.
Graphical abstract: Highlights: Expression for maximum retention concentration for monolayer of multi-sized fines. Translation of fines test data with varying salinity into those with velocity variation. Kaolinite and illite/chlorite fines are responsible for permeability decline in the tests. Significant permeability decline during fines migration with water salinity decrease. Increased fines release and permeability impairment at geothermal temperatures. Abstract: Fines migration with consequent well productivity reduction is a well-known phenomenon occurring during exploitation of geothermal reservoirs. Laboratory corefloods with piecewise constant decreasing ionic strength have been performed with measurements of the pressure drop along the core and the accumulated effluent particle concentration. The tests were performed under ambient conditions with further results re-calculation for high geothermal temperatures. Permeability stabilises after injection of numerous pore volumes, suggesting slow drift of mobilised particles if compared with the carrier water velocity. SEM-EDX analysis of the produced fine particles shows that kaolinite and illite/chlorite are the major minerals responsible for the permeability damage. The competitive effects of decreasing water viscosity and weakening electrostatic attraction on the attached particle concentration during temperature increase have been observed. The micro modelling of the fine particle mechanical equilibrium shows that the electrostatic attraction effect on the fines attachment dominates. It results in increased fines detachment and permeability decline at high temperatures, suggesting that geothermal fields are more susceptible for fines migration formation damage than the conventional oilfields and aquifers. A new "ionic strength- velocity" translation procedure is developed for determining velocity dependency of the maximum retention function from laboratory coreflood tests with varying ionic strength. Experiment-based evaluation of velocity- and temperature-dependencies on the maximum retention function is demonstrated for specific conditions of geothermal resevoirs. We discuss well inflow performance with fines migration, and derive an exact solution for axi-symmetric water-flow towards the well. The solution includes explicit formulae for attached, suspended and strained fines, and well productivity. The analytical model along with the obtained laboratory data allows successful matching of the well discharge history (Salamander geothermal field, Australia).